2014
DOI: 10.1002/etc.2718
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods for toxicity assessments in fish: Comparison of the fish embryo toxicity and the larval growth and survival tests in zebrafish and fathead minnows

Abstract: An increased demand for chemical toxicity evaluations has resulted in the need for alternative testing strategies that address animal welfare concerns. The fish embryo toxicity (FET) test developed for zebrafish (Danio rerio) is one such alternative, and the application of the FET test to other species such as the fathead minnow (Pimephales promelas) has been proposed. In the present study, the performances of the FET test and the larval growth and survival (LGS; a standard toxicity testing method) test in zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…Survival among control embryos exceeded 90% in each of the 3 FET test replicates. The mean LC50 value (± standard deviation) was estimated at 8.8 ± 2.7 mg DCA/L, a value consistent with previously reported DCA LC50 values, which range from 4.4 to 9.6 mg DCA/L (Braunbeck et al ; Böhler ; Jeffries et al ). None of the embryos in the 16 mg DCA/L group survived the duration of the FET test, and thus, sublethal endpoints were not measured in embryos from this group.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Survival among control embryos exceeded 90% in each of the 3 FET test replicates. The mean LC50 value (± standard deviation) was estimated at 8.8 ± 2.7 mg DCA/L, a value consistent with previously reported DCA LC50 values, which range from 4.4 to 9.6 mg DCA/L (Braunbeck et al ; Böhler ; Jeffries et al ). None of the embryos in the 16 mg DCA/L group survived the duration of the FET test, and thus, sublethal endpoints were not measured in embryos from this group.…”
Section: Resultssupporting
confidence: 89%
“…Methods for a fathead minnow FET test have already been developed (Braunbeck et al ), and studies have shown that the sensitivity of the fathead minnow FET test is comparable to that of other test methods, including the larval growth and survival test, for some chemical classes (Braunbeck et al ; Jeffries et al , 2015; Roush et al ), suggesting that the fathead minnow can be used as a FET test species. In addition, previous studies have provided evidence that metrics of growth (i.e., growth‐related gene expression, wet wt, and length), neurological dysfunction (i.e., neurological‐related gene expression, spontaneous contraction frequency, and eye size), and cardiovascular dysfunction (i.e., cardiovascular system–related gene expression, heart rate, and pericardial edema) in embryos and eleutheroembryos may be sensitive to contaminant‐induced alterations (Cheng et al ; Antkiewicz et al ; Usenko et al ; Chen ; Incardona et al ; Jeffries et al ; Roush et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Each test included a positive control group exposed to the reference toxicant, 3,4-dichloroanile (DCA). Stock solutions of 100 mg/L were prepared in dechlorinated water using DCA (Sigma-Aldrich), as described in Sellin Jeffries et al [8]. Tests with mock MWWTP effluents included an ammonia-exposed positive control group as well as an effluent-only group (exposed to MWWTP effluents that had not been spiked with ammonia), in addition to the DCA-exposed positive control group.…”
Section: Test Chemicals and Mock Effluentsmentioning
confidence: 99%
“…Fathead minnows and zebrafish were obtained according to the procedures outlined in Sellin Jeffries et al [8]. Briefly, early-life stage zebrafish and fathead minnows for use in the FET and LGS tests were obtained from sexually mature adult zebrafish purchased from Aquatica BioTech (Sun City Center) or fathead minnows from Miami University's in-house culture (originally stocked using fish obtained from Aquatic Biosystems and the USEPA Research Facility [Cincinnati, OH]).…”
Section: Production Of Embryos and Eleutheroembryosmentioning
confidence: 99%
See 1 more Smart Citation